The effect of partial slip on the wear rate of rails - Alwahdi, F.; Franklin, F.J.; Kapoor, A. (Wear, 2005)
The tractive force transmitted through the contact of rail and wheel is often lower than the limiting friction force and such contacts are not fully slipping. The distribution of traction is no longer proportional to the distribution of normal pressure in the contact patch. The distribution of stress in the rail, and therefore also the shakedown limit and the ratchetting wear rate, is affected as a result. A computer model, which simulates the ratchetting wear of a ductile material subject to repeated loading, is used to investigate the effects of partially slipping contacts on the wear rate of rail material for a range conditions appropriate for rail/wheel contact. Particular emphasis is placed on the strain-hardening properties of the rail material. Wear rate is found to increase with traction coefficient for constant friction coefficient, indicating the importance of both parameters for the wear rate of rails.